The cave book - Silvestru, Emil. (Green Forest, Ark. : Master Books, 2008)
Discusses the history of cave exploring, the thriving ecology, animals that live there, and famous caves around the world.
Humans and caves -- Caves and mythology -- Caves and karst -- Classifying caves -- Exploring caves -- Studying caves.
Includes fold-out poster on p. [81].
Includes bibliographical references (p. 73) and index.
Keywords: Creationism; Christian education